Sustainable education for refugee children: a quasi experimental study - Jamaludin, Thandar Soe @ Sumaiyah; Nurumal, Mohd. Said; Hassan, Masmunaa (2023)
Background: The refugee children are unable to access the formal education like public schools due to their status with no citizenships. According to sustainable development goals (SGDs), everyone should have equal access to formal education. Objective: This study aimed to evaluate the effectiveness of sustainable education programme for refugee children. Method: An educational programme was provided to refugee children by using a quasiexperimental approach with 27 refugee children with a period of 1 year. Findings: It was found that the learning activities of refugee children were improved after attending the educational programme. Besides, their parents’ satisfaction level also increased. Conclusion: Spreading awareness regarding the refugees’ education issue should be conducted more effectively in the future. Aside from rising awareness among the society, it is also important to convince the refugee parents of the importance of education towards their children.